OWE-021 Describing the gut microbiome and metabolomic changes in bile acid diarrhoea. (8th June 2018) - Sagar, Nidhi; Duboc, Henri; Kay, Gemma; Gerasimidis, Konstantinos; Svolos, Vaios; Wicaksono, Alfian; Quince, Christopher; Covington, James; O'Connell, Nicola; Wurie, Subiatu; Arasaradnam, Ramesh
Abstract : Introduction: The diagnosis of bile acid diarrhoea (BAD) is often missed or misdiagnosed for irritable bowel syndrome – diarrhoea predominant (IBS-D) as these conditions have a similar clinical presentation. The principal hindrance to diagnosis of BAD is limited access to the diagnostic SeHCAT scan. Mechanisms of aetiology underlying BAD have not been fully elucidated but it has been accepted that bile acids (BAs) are metabolised by the gut microbiota, therefore their role as signalling molecules in regulating intestinal homeostasis is influenced primarily by the gut commensals. The aim was to profile the gut microbiome in BAD and investigate the mechanisms of how bacterial metabolic products may influence the development of disease. Methods: 157 patients participated in the study after having a SeHCAT scan to either diagnose BAD or IBS-D (the latter with a negative scan). Exclusion criteria included recent use of antibiotics/probiotics and the diagnoses of coeliac disease, colorectal cancer and active inflammatory bowel disease (unremarkable levels of C-reactive protein and/or faecal calprotectin were required) in type 1 BAD patients. To examine the gut microbiome, 16S ribosomal RNA gene analysis was undertaken. Bacterial metabolites (short chain fatty acids-SCFAs and volatile organic compounds-VOCs) and BAs were measured using gas and liquid chromatography, mass and ion mobility spectrometry. Results: Intestinal dysbiosis with reduced bacterial diversity was observed in patients with BAD compared with IBS-D (p=0.01). A greater total concentration of SCFAs (p=0.17) with increases in the concentrations of acetate (p=0.14) and propionate (p=0.08) were observed in BAD compared to IBS-D. An increase in the concentrations of faecal primary BAs (p=0.05) and serum CDCA (p=0.05) was observed in BAD compared to IBS-D. Conclusions: Intestinal dysbiosis with altered fermentation and resultant BA dysmetabolism were observed in BAD. The metabolic output of the microbiota rather than abundance of specific bacterial taxa appears to be more important in the aetiology of BAD.